Simultaneous, time-resolved measurements of OH and HO2 radicals by coupling of high repetition rate LIF and cw-CRDS techniques to a laser photolysis reactor and its application to the photolysis of H2O2 - Parker, A. E.; Jain, C.; Schoemaecker, C.; Szriftgiser, P.; Votava, O.; Fittschen, C. (Applied physics. B, Lasers and optics, 2011)
A new experimental set-up for the simultaneous, time-resolved measurement of OH and HO 2 radicals by coupling high repetition rate Laser Induced Fluorescence (LIF) and cw-Cavity Ring-Down Spectroscopy (cw-CRDS) detection techniques to a laser photolysis reactor has been installed. The first experiments concern the well-known photolysis of H 2 O 2 : the absorption cross sections of H 2 O 2 lines in the near-infrared at 6636.75 and 6639.90 cm −1 have been determined by combined results of spectroscopic and kinetic measurements of OH and HO 2 radicals produced by the photolysis of H 2 O 2 at 248 nm. These experiments will enable the measurement of absolute H 2 O 2 concentrations in future experiments with the same set-up.